Performance pedagógica dos tutores da UAB/UFSM: princípios para um processo ensino-aprendizagem criativo - Schraiber, Rogério Tubias (2018)
The Pedagogical Performance of Tutors (PPT) of the Universidade Aberta do Brasil (UAB), at the Universidade Federal de Santa Maria (UFSM), that was the main research topic, based in the great Education area. The E-learning in higher education was the context. Investigating how the PPT of postgraduate courses, at UAB/UFSM in a Specialization level, could potentiate the development of a Creative Learning- Teaching Process (CLTP) was the problem that directed us. As a general objective, we wish to understand the principles of PPT of the UAB/UFSM that can enhance the development of a CLTP. We found theoretical basis in the Performance Studies, by Richard Schechner and Victor Turner and in the teaching performance studies, by Mallmann (2008). Methodologically, we systematized a Case Study producing data with tutors through questionnaires, interviews, observations, e-mail, reading documents, messages and images obtained by social networks (Facebook and WhatsApp). In the analytical model, we consider the procedures of the Discursive Textual Analysis (DTA) that, after the unitarization phase, originated the categories Technological-Pedagogical Fluency (TPF), Creativity, Educational Social Skills (ESS), Interaction and collaboration and Presentiality, which are broadly interwoven in the PPT, defining the framework for the conceptual proposition of this research. Conclusively, we consider that these categories, by enabling the development of pedagogical strategies, constitute, in the PPT, the principles capable of enhancing a CLTP.